Evidence Supports The Formation Of Isoimides Derived From Pyromellitic Dianhydride - Hussein, Shaymaa T.; Ali, Emad T.; Ali, Khalid F.; Tomma, Jombod H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Some new mono isoimides of asymmetrical pyromillitdiimide derived from pyromellitic dianhydride were synthesized and studied by their melting points , FTIR , and 1HNMR spectroscopy and C.H.N analysis (for some of them) and it was proved that the mechanism of the formation of these isoimides followed , the mechanism suggested by Cotter et al . by using N, Nâ”€- dicyclohexylcarbodiimide as dehydrating agent , in spite of the groups attached to the phenyl moiety as mentioned in literatures .